Efeito prebiótico de suco de caju (Anacardium occidentale) contendo glico-oligossacarídeos, dextrana e tagatose - Leite, Ana Karoline Ferreira (2020)
The intestinal microbiota plays an important role in the health of the host and dietary supplementation with prebiotics can improve their balance. Fruit juices can be considered ideal vehicles for the consumption of prebiotics, because they are rich in bioactive compounds and have good acceptability by consumers. In the specific case of the production of prebiotic juices through the synthesis of oligosaccharides, it is necessary to restore the sweetness of the drinks because the sugars are consumed during the synthesis. Thus, the objective of the present work was to evaluate the prebiotic effect of prebiotic cashew juices, sweetened or not with tagatose. The prebiotic oligosaccharides were synthesized in the juice, with or without agitation, by the enzyme dextransucrase (30 ° C / 17 h). An in vitro simulated digestion was carried out at 37 ° C/6 h. During the passage through the gastrointestinal tract, the concentration of glyco-oligosaccharides, dextran and tagatose, and the bioaccessibility of vitamin C were evaluated. To evaluate the prebiotic effect of the functional juices, the following probiotic microorganisms were used: Lactobacillus casei, Bifidobacterium breve and Bifidobacterium infantis. The results showed that oligosaccharides, tagatose and part of the dextran (70 - 90 %) were resistant to gastrointestinal conditions and reached the final part of the digestive system where the consumption of prebiotic carbohydrates by probiotic microorganisms occurs. In addition, juices containing these prebiotics have improved the bioaccessibility of vitamin C, which suggests a protective effect offered by these ingredients. The ingredients with prebiotic properties acted as substrates and stimulated the growth of bifidobacteria and lactobacilli. However, each microorganism presented its particularities and consumed some of these components preferentially. Tagatose proved to be a good substrate for the multiplication of B. infantis. Conversely, L. casei and B. breve deserve to be highlighted for preferentially metabolizing dextran and oligosaccharides, respectively. The concentrations of components with prebiotic properties of the juices varied between 2.68 and 10.23 g / 250 mL of juice. Finally, the cashew juices produced in this work meet the claimed of functional appeal, given that they had a prebiotic effect by stimulating the growth of beneficial microorganisms.